Experimental verification of smart grid control functions on international grids using a real-time simulator - Palaniappan, Rajkumar; Molodchyk, Oleksii; Shariati-Sarcheshmeh, Mahdi; Asmah, Marilyn Winifred; Liu, Jiayan; Schlichtherle, Tobias; Richter, Frank; Kwofie, Ekow Appiah; Festner, Daniel Rios; Blanco, Gerardo; Mutule, Anna; Borscevskis, Olegs; et al. (Technische Universität Dortmund, 2022)
The drastic increase in distributed energy resources (DERs) leads to challenges in the operation of distribution systems worldwide. While several solutions for grid monitoring and control are available on the market and in literature, this research is the first of its kind aiming to supervise the grid by providing a modular configurable unified hardware and software architecture. The control algorithms are configured using data models according to IEC 61850-7-3 and IEC 61850-7-4. The novel system architecture is a portable, modular and flexible architecture that aggregates smart grid control functions onto a standardised hardware platform, emphasising the need for hardware independence. The central controller contains several smart grid control functions and the various field devices are distributed across the distribution grid. This paper deals with the simulation of different real-world distribution grids on the Real-Time Simulator (RTS) and experimental verification of the control algorithms. Smart grid control functions such as Coordinated Voltage Control (CVC) and Optimal Power Flow (OPF) are experimentally verified on a German grid. The grid dynamics are compared when the central controller executes the CVC against the OPF implementations. The experimental results, advantages and challenges of each control are presented here. The results also showed the variation in grid behaviour when the control parameters were varied. The paper also shows that the algorithm and the choice of the control parameters depend upon the distribution grid's complexity and the system operator's individual needs. The results illustrate the potential of such a universal distribution automation solution for system operators worldwide.
IET generation, transmission & distribution;16(13)
Keywords: 620; Intelligentes Stromnetz; Elektrizitätsversorgungsnetz; Netzstabilität <Elektrische Energietechnik>; Echtzeitsimulation; Internationaler Vergleich; Dezentrale Energieversorgung; Erneuerbare Energien; IEC-Norm